TMEM100, a regulator of TRPV1-TRPA1 interaction, contributes to temporomandibular disorder pain - Wang, Peng; Zhang, Qiaojuan; Dias, Fabiana C.; Suttle, Abbie; Dong, Xinzhong; Chen, Yong (Frontiers in Molecular Neuroscience, 2023)
There is an unmet need to identify new therapeutic targets for temporomandibular disorder (TMD) pain because current treatments are limited and unsatisfactory. TMEM100, a two-transmembrane protein, was recently identified as a regulator to weaken the TRPA1-TRPV1 physical association, resulting in disinhibition of TRPA1 activity in sensory neurons. Recent studies have also shown that Tmem100, Trpa1, and Trpv1 mRNAs were upregulated in trigeminal ganglion (TG) after inflammation of the temporomandibular joint (TMJ) associated tissues. These findings raise a critical question regarding whether TMEM100 in TG neurons is involved in TMD pain via regulating the TRPA1-TRPV1 functional interaction. Here, using two mouse models of TMD pain induced by TMJ inflammation or masseter muscle injury, we found that global knockout or systemic inhibition of TRPA1 and TRPV1 attenuated pain. In line with their increased genes, mice exhibited significant upregulation of TMEM100, TRPA1, and TRPV1 at the protein levels in TG neurons after TMD pain. Importantly, TMEM100 co-expressed with TRPA1 and TRPV1 in TG neurons-innervating the TMJ and masseter muscle and their co-expression was increased after TMD pain. Moreover, the enhanced activity of TRPA1 in TG neurons evoked by TMJ inflammation or masseter muscle injury was suppressed by inhibition of TMEM100. Selective deletion of Tmem100 in TG neurons or local administration of TMEM100 inhibitor into the TMJ or masseter muscle attenuated TMD pain. Together, these results suggest that TMEM100 in TG neurons contributes to TMD pain by regulating TRPA1 activity within the TRPA1-TRPV1 complex. TMEM100 therefore represents a potential novel target-of-interest for TMD pain.